Muslim Religiosity and Pro-Environmental Behavior: Literature Review from a Psychological Perspective - Rahmanto, Septian Wahyu (International Conference on Sustainable Health Promotion, 2023)
Religiosity is among the most important cultural forces and significantly influences Muslim behavior. Muslim religiosity can play a role as an essential factor influencing pro-environmental behavior. This study aims to analyze previous studies related to Muslim religiosity and pro-environmental behavior using a literature review technique. Data was obtained by searching journal article data on Google Scholar for the last five years (2019-2023). The keywords are religiosity, Muslim, pro-environmental behavior, and environmental ethics. Relevant data were analyzed with a descriptive approach and synthesis of the literature. A total of 94 articles were found from the search; after identification, screening, and eligibility processes were carried out, 7 articles were obtained that met the inclusion criteria and were by the research objectives. Furthermore, the analysis findings are divided into (1) the dynamics of Muslim religiosity towards pro-environmental behavior and (2) other factors that contribute to Muslim pro-environmental behavior. The results of this study are expected to provide insight into developing programs and policies that promote pro-environmental behavior in the Muslim community.